Answers

2014-07-01T14:53:11+05:30
Elimination MethodThe way to eliminate that variable is to add the 2 equations as so: 4x + y = 13 + 5x - y = 14 We would get the following general equation: 9x = 27 
Substitution Method When you are given a systems of equations where one variable is given an expression, you can use this substitution method.
0
2014-07-01T15:14:58+05:30
If the equations are x+y=9 and 3x+2y=5
by elimination meathod
3x+2y=5
 x+y=9   (mulltiply 3 to both sides)
3x+2y=5
3x+3y=27
subtract
-y=   -22
y=22
x+22=9
x=9-22
x=  -13
by substitution method
x+y=9
x=9-y
put value in second equation
3(9-y)+2y=5
27-3y+2y=5
27-y=5
-y=-27+5
-y=  -22
y=22
x=9-y
x=9-22
x= -13
0
please mark as the best
my teacher told me this...sorry